Hybrid Films: Kirigami‐Inspired Deformable 3D Structures Conformable to Curved Biological Surface (Adv. Sci. 12/2018). Issue 12 (19th December 2018) - Yang, Chao; Zhang, Heng; Liu, Youdi; Yu, Zhongliang; Wei, Xiaoding; Hu, Youfan
Abstract : In article number1801070, Youfan Hu and co‐workers construct 3D deformable electronic systems for physiological monitoring on curved surfaces by utilizing silver nanowires/parylene hybrid films in a way inspired by kirigami. Unique patterning procedures and rational cut designs are combined to transform planar electronic systems into a tunable 3D form. As an example, a deformable transparent humidity sensor for sweat monitoring was demonstrated on an elbow and finger joint.